2020
DOI: 10.1590/s1678-86212020000400457
|View full text |Cite
|
Sign up to set email alerts
|

Influência da umidade do ar no conforto térmico de usuários de edificações de escritórios em Florianópolis/SC

Abstract: Resumo O conforto térmico apresenta elevada importância para a conservação de energia em edificações, bem como para a satisfação e o desempenho dos usuários. O principal objetivo deste trabalho é avaliar o efeito da umidade do ar no conforto térmico de usuários de edificações de escritórios localizadas no clima subtropical úmido de Florianópolis/SC. Com base em dados previamente coletados em campo, foram efetuadas análises estatísticas considerando a umidade do ar e as respostas subjetivas dos usuários obtidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For this purpose, each user subjective response was combined with the corresponding environmental conditions. This study considered the absolute humidity for the analyses involving humidity, as suggested by some authors [28,37,38], since the relative humidity is associated with air temperature. According to ISO 7726:1998 [39], absolute humidity can be calculated based on the measurements of air temperature and relative humidity, being expressed through the partial pressure of water vapour or the humidity ratio.…”
Section: Data Contextualisation and Statistical Analysesmentioning
confidence: 99%
“…For this purpose, each user subjective response was combined with the corresponding environmental conditions. This study considered the absolute humidity for the analyses involving humidity, as suggested by some authors [28,37,38], since the relative humidity is associated with air temperature. According to ISO 7726:1998 [39], absolute humidity can be calculated based on the measurements of air temperature and relative humidity, being expressed through the partial pressure of water vapour or the humidity ratio.…”
Section: Data Contextualisation and Statistical Analysesmentioning
confidence: 99%